PS-BPB07-4: LONG-TERM PATHOLOGICAL CHANGES IN ABLATED RENAL NERVES FOLLOWING CATHETER-BASED RADIOFREQUENCY RENAL DENERVATION IN A NORMOTENSIVE SWINE MODEL. (January 2023) - Schlaich, Markus; Tunev, Stefan; Sharp, Andrew; Lee, David P; Finn, Aloke; Trudel, Julie; Kandzari, David E
Abstract : Objective: Randomized, sham-controlled clinical trials with catheter-based radiofrequency (RF) renal denervation (RDN) have demonstrated safety and efficacy of the procedure through 3 years. However, pre-clinical reports of functional renal nerve regrowth are inconsistent. In this analysis in normotensive swine, we assessed the specificity of RF ablation around the renal arteries out to 28 days and quantified the long-term pathophysiological outcomes through 180 days. Design and method: RF ablations were delivered to the renal arteries of normotensive swine using the Symplicity SpyralTM catheter (Medtronic, Santa Rosa, CA, USA). For the tissue specificity analysis, RF RDN was performed in 14 swine, and serial sections of the renal artery were harvested from 6 pigs at day 7, and 8 pigs at day 28. Surrounding anatomic tissues of the treated areas (including ureter, kidney, lymph nodes, skeletal muscle, adrenal glands, and renal nerves) were evaluated in response to RDN using a semi-quantitative scoring system (Figure). To assess durability, RF RDN was performed in a separate group of 14 normotensive swine, with an additional 14 pigs serving as control. Serial sections of renal artery were harvested at day 7 (n = 6 animals per group) and day 180 (n = 8 per group) post-procedure. In addition, matrixed samples from renal cortex were collected for each pig in both studies and subjected to bioanalytical quantification of cortical norepinephrine (NE) levels and immunohistochemical analysis of renal cortical axon density. Results: At 7 and 28 days, cell disruption in non-target perivascular tissues (ureter, kidney, lymph nodes, skeletal muscle and adrenal glands) were rare/absent, whereas renal artery nerve disruption and axonal loss were sustained through 28 days (Figure). Through 180 days, nerve atrophy due to axonal destruction was apparent within and downstream to the ablation regions. Consistent nerve necrosis at the ablation sites was evident at day 7, but not day 180. Fibrosis was confined to the ablated regions at 7 and 180 days. Renal cortical axon density and corresponding cortical NE levels were significantly reduced at 7 and 180 days in the RF RDN group vs. control. Conclusion: RF RDN specifically disrupted the renal nerves around the renal artery leading to downstream axonal loss in the renal cortex. Renal cortical axon density, associated NE reduction, and nerve atrophy due to axonal destruction were sustained through 180 days post-RDN in a normotensive swine model. These results support the existing clinical evidence of specific and durable effects of RF RDN in lowering blood pressure.